Trends of tabloid journalism in Kazakhstan (Herald of Journalism, 2021)
The purpose of this paper is to study the evolution and social role of tabloid journalism in Kazakh- stan. The process of tabloidization involves destruction of traditional ideals, as well as raising social questions previously considered as “taboo”. The history of formation, the forecast for future development of tabloid journalism in a single country with modern media technologies is a very rare topic for the Central Asian region. The scientific and practical significance of the study lies in its novelty and the lack of similar works. To investigate the current place of tabloid journalism in the media space of Kazakhstan, a number of well-known Kazakhstan-based journalists, editors, opinion makers and bloggers were inter- viewed. The survey involved 100 people.Questionnaire results were analysed manually. According to the results, a possible reason of load development is the mentality that does not allow local journalists to write about the personal lives of public figures. At the same time, it is obvious that there is a new perspective for tabloid journalism in relation to the public sphere. The practical value of the study is lies in identification the main problems in this area. Many Kazakhstani media that, according to the criteria, could be considered tabloids, do not declared themselves as such, because of the possible fall in the image. It is also interesting to con- sider Kazakhstani tabloid trends, which are influenced to a significant degree by economic, rather than political, factors. Thus, it appears that the development of characteristics of tabloid journalism is at the forefront of market-driven journalism. So, knowing the main problems of the media sector, it will be easier to show the prospects for its development.Key words: Kazakhstan, tabloid media, journalism, democracy.